Plan exportador de chaquetas de cuero, de la empresa comercializadora Belier S.A.S de la ciudad de Tunja (2020)
The research carried out in this document on Comercializadora Belier S.A.S, is dedicated to the manufacture and marketing of articles derived from leather and has been operating in the Colombian market for five years. The company developed this export plan, identifying the Peruvian market as a target market for leather jackets. It set goals; The exportable supply capacity is identified, the client abroad was identified, and the entire export logistics process was identified, and the cost matrix corresponding to the product to be exported, leather jackets was made. The export plan resulted in the company Alessandro Ferragamo, located in the city of Lima, which makes the logistics process easier for the company, since the port of entry in Callao, being 1 hour away by land transportation from the city from Lima. For the company Belier SAS, it is an excellent opportunity, since it allows it to internationalize, show the quality of the Colombian product, growth within the company, development and obtaining technology to be more competitive.